Effect of combined oral contraceptives on menstrual migraine frequency and severity: a narrative review - Yethindra Vityala; Ruchika Garg; Samina Ausvi; Manjula Shantaram; Srikanya Tippabathini; Lekhashree Hosur Brahmananda Reddy; Yash Jain; Pavani Jaladi; Sai Praneeth Duvvuri; Krishna Chaitanya Meduri (Exploration of Drug Science)
Migraine, a commonly occurring neurological disorder, disproportionately affects women during their reproductive years, and its symptoms are often intensified by hormonal fluctuations. This narrative review examines the impact of hormonal contraceptives, particularly combined oral contraceptives (COCs), on menstrual migraine (MM). This review assessed the impact of COCs on MM through a literature search in PubMed, Google Scholar, Web of Science, and Scopus using keywords like “menstrual migraine”, “hormone therapy”, and “COCs”. The selection criteria were peer-reviewed studies published between 2014 and 2024, written in English, and focused on MM treatment with COCs. Exclusion criteria were duplicates, editorials, irrelevant articles, and non-English studies. The literature reveals inconsistent results, with some studies reporting aggravation of migraine symptoms with COC use, whereas others indicate a decrease in the frequency and severity of attacks, especially with continuous use. Factors affecting these outcomes include patient age, menstrual cycle characteristics, and migraine type. It is crucial to choose contraceptives that suit individual patient profiles, considering the potential for increased migraine frequency or onset of migraine with aura in some women. Further studies are required to establish clear clinical guidelines. It is recommended to create personalized treatment plans that balance the effectiveness of migraine management with the overall health risks.